Vibrant Architecture. Matter as a CoDesigner of Living Structures (2015)
This speculative narrative serves as a design exploration that extends the ecological and cultural implications of vibrant matter within the city of Venice from the perspective of its inhabitants, which include human and non-human communities. This story was written and performed for the Meta.morf conference at the second Trondheim Biennale (Meta.morf, 2012b).